THEORETICAL BASES OF INFORMATION AND INTELLECTUAL COMPETENCE OF FUTURE TEACHERS OF INFORMATICS - Shayakhmetova А.С.; Othman М.; Seisenbekova П.Б. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
This article reviews the research of scientists on general information and intellectual competence and gives a definition of information and intellectual competence. The possibility of digitization of education for the formation of information and intellectual competence of future teachers of computer science was studied. The structure of the information and intellectual competence of the future teacher of computer science is theoretically substantiated and formulated. The information and intellectual competencies of students were determined by the criteria of knowledge, skills and potential and presented in tabular form. The sample questions to determine the information and intellectual competence of students are based on knowledge mobility, method flexibility and critical thinking. To perform the situational task, we divided the level of performance of students into informational, improvisational, heuristic, considered laboratory work at the information level, independent work of the student with the teacher at the improvisational level and independent work of the student at the heuristic level. A generalized algorithm for the formation of information and intellectual competencies of students in the context of digitalization of education has been developed.